Electronic structure of spherical quantum dots using coupled cluster method - Heidari, Ideh; Pal, Sourav; Pujari, B. S.; Kanhere, Dilip G. (Journal of Chemical Physics, 2007)
2, 6, 12, and 20 electron quantum dots have been studied using coupled cluster at singles and doubles level and extensive multireference coupled cluster (MRCC) method. A Fock-space version of MRCC (FSMRCC) containing single hole-particle excited determinants has been used to calculate low-lying excited states of the above system. The ionization potential and electron affinity are also calculated. The effect of correlation energy on excitation energy and charge density is shown by calculating them at the high density region (low value of density parameter r(s)) and at the low density region (high value of density parameter r(s)). (c) 2007 American Institute of Physics.

Growth and structural properties of Mg-N (N=10-56) clusters: density functional theory study - Heidari, Ideh; De, Sandip; Ghazi, S. M.; Goedecker, Stefan; Kanhere, Dilip G. (Journal of Physical Chemistry A, 2011)
Using the minima hopping global geometry optimization method on density functional potential energy surface, we have studied the structural and electronic properties of magnesium clusters for a size range of Mg-N where N = 10-56. Our exhaustive search reveals that most of our global minima are nonsymmetric in the size range above N = 20. We elucidate the evolutionary trend of the entire series and present more details about the peculiar growth of the clusters. For N> 20, it is possible to divide the cluster into two regions: the core region and the surface region. It turns out that the growth follows a peculiar cyclic pattern where the core and surface grow alternatively. The surface energy, as a function of number of atoms shows a clear signature as the number of atoms in the core increases by one. We have also carried out stability analysis and the stable sizes(magic numbers) agree very well with the experimental magic numbers reported by Diederich [J. Chem. Phys. 2011, 134, 124302]. We point out the similarities and differences between our results and sodium clusters.

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.